2021
DOI: 10.1186/s12891-021-04621-x
|View full text |Cite
|
Sign up to set email alerts
|

The compensatory mechanisms for global sagittal balance in degenerative spinal kyphosis patients: a radiological analysis of muscle-skeletal associations

Abstract: Background The position of the head relative to the spine can be used to evaluate the true global balance in patients with degenerative spinal kyphosis (DSK). However, it is still not clear how the position of the head is related to the spinal-pelvic parameters and lumbar muscles, which are most commonly considered. Methods Sixty-seven patients with DSK admitted in the hospital from January 2017 to January 2019 were retrospectively analyzed. All pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 41 publications
2
7
0
Order By: Relevance
“…Moreover, the aforementioned factors may have contributed to deviations of the anteroposterior spinal curvatures were found in the majority of participants (especially thoracic hyperkyphosis and lumbar hypolordosis). The results of our study correspond with the findings of Xia et al (2021) who reported a relationship between upper and lower sagittal compensatory mechanisms, in which the head position relative to the spine was significantly correlated with spinal-pelvic variables and lower lumbar muscles. Considering the factors related to the prevalence and location of musculoskeletal pain in sitting volleyball players, our results indicate that excessive fat mass (assessed by the corrected BMI, i.e., Brown-Fisher rate) impacted wrist pain in athletes with lower limb deficiency.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Moreover, the aforementioned factors may have contributed to deviations of the anteroposterior spinal curvatures were found in the majority of participants (especially thoracic hyperkyphosis and lumbar hypolordosis). The results of our study correspond with the findings of Xia et al (2021) who reported a relationship between upper and lower sagittal compensatory mechanisms, in which the head position relative to the spine was significantly correlated with spinal-pelvic variables and lower lumbar muscles. Considering the factors related to the prevalence and location of musculoskeletal pain in sitting volleyball players, our results indicate that excessive fat mass (assessed by the corrected BMI, i.e., Brown-Fisher rate) impacted wrist pain in athletes with lower limb deficiency.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the aforementioned factors may have contributed to deviations of the anteroposterior spinal curvatures were found in the majority of participants (especially thoracic hyperkyphosis and lumbar hypolordosis). The results of our study correspond with the findings of Xia et al (2021) who reported a relationship between upper and lower sagittal compensatory mechanisms, in which the head position relative to the spine was significantly correlated with spinal-pelvic variables and lower lumbar muscles.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…28 However, the C7 plumb line was found to be poorly correlated with GL, 11 and it has been well-studied that head balance, the cervical spinal curve, and lower limbs also contribute to the global balance of the spine although these factors are not incorporated in the C7-SVA concept. 9,20,21 The center of gravity, or GL, is an important concept, for which only a few studies have been conducted on normal values. 12,14 Humans maintain their posture with the available musculature and joints while not harming the purpose of horizontal gaze.…”
Section: Discussionmentioning
confidence: 99%
“…However, numerous radiographic parameters investigated to date cannot consistently predict MF. 9,[19][20][21] Even patients with ASD with well-corrected sagittal alignment parameters in SRS-Schwab or global alignment and proportion criteria sometimes develop MF, which reflects the limitation of parameters mostly involving the fixed segments only. 22 The need has arisen for a perspective to better understand spinal balance that also incorporates unfused spinal segments with a dynamic compensatory capacity and the chance of further degeneration.…”
Section: Discussionmentioning
confidence: 99%